Proceedings of the International Conference on Soft Computing Systems ICSCS 2015, Volume 2 - Suresh, L. Padma; Panigrahi, Bijaya Ketan (Advances in Intelligent Systems and Computing,, 2016)
The book is a collection of high-quality peer-reviewed research papers presented in International Conference on Soft Computing Systems (ICSCS 2015) held at Noorul Islam Centre for Higher Education, Chennai, India. These research papers provide the latest developments in the emerging areas of Soft Computing in Engineering and Technology. The book is organized in two volumes and discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques. It presents invited papers from the inventors/originators of new applications and advanced technologies.